The Senegal PICOGERNA - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
The Integrated Protect for the Conservation and Management of Natural Resources (PICOGERNA) was started in Senegal in 1990 but had to be terminated in 1993 following the Khelkom affair (the classified forest given to the Mourides General Caliph for...